Tingkat pemanfaatan ikan kaci-kaci (Diagramma pictum) pada perairan Mapur yang didaratkan di Desa Kelong, Kabupaten Bintan, Indonesia - Febrianti Lestari; Jupitar Jupitar; Susiana Susiana (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2020)
Mapur waters is one of the potential areas for demersal fish distribution in Bintan waters. The purpose of this study was to investigate the effort of catching painted sweetlips fish (Diagramma pictum), Maximum Sustainable Yield of Painted Sweetlips Fish and investigated the amount of Painted Sweetlips Fish catches allowed (JTB). The research method used is the survey method, which is direct observation at the research location by recording fishing operations such as fishing gear and catches through direct interviews with fishermen working in fish storage warehouses. Data taken in the form of primary data and secondary data. The results showed that the effort of catching Painted Sweetlips Fish on Mapur waters was 314.00 units, with the MSY value was 713,016 kg/unit. So that the amount of catch allowed (JTB) is 80% from MSY which is equal to 570.41 kg/unit, with the utilization rate of Painted Sweetlips Fish on which is equal to 89%.